Cultural and technological Synergy: A new Pathway to learners success in development studies in Lesotho secondary schools - Musa Adekunle Ayanwale; Mathaha Puseletso (Social Sciences and Humanities Open)
Efforts to improve learners' achievement in Development Studies (DS) have been ongoing, yet the chief examiners' reports from 2018 to 2023 show no significant improvement. This persistent issue may be linked to the use of inappropriate pedagogical practices. There is a notable lack of research exploring the Culturo-Techno-Contextual Approach (CTCA) in Southern Africa; hence, we investigated how CTCA can enhance learners' achievement in DS classrooms. Grounded in socio-constructivism, practice architecture, and meaningful verbal learning theory, a quasi-experimental design involving grade 11 intact classes was employed to generate quantitative data. We employed an Analysis of covariance (ANCOVA) to assess the impact of CTCA on learners' achievement and mean ranks were calculated to determine the difficulty levels of DS topics. The results indicate that the most challenging topic was theories of development (M = 4.72), followed by Population and Development (M = 3.71). More importantly, learners exposed to CTCA significantly outperformed their peers in the comparison group, as evidenced by [F (1,47) = 4.579; p < 0.05] n2 = .89 (p = 0.038). These results suggest that CTCA positively impacts learners' achievement, particularly in Population and Development. Continuous assistance and active participation were associated with higher scores and better comprehension. We conclude that incorporating CTCA in DS teaching can improve learner outcomes. These results underscore the need for adopting innovative pedagogical approaches like CTCA to enhance educational practices and learner achievement in DS.